Older Adults Reporting More Diabetes Care Have Greater 9-year Survival - Han, Benjamin H. (J Am Geriatr Soc, 2015)
OBJECTIVES: Delivery of recommended diabetes care processes has improved nationally but it is unclear if there is any association with improved survival in middle-aged and older adults with diabetes. We hypothesized that receiving more recommended diabetes care processes would translate into better 9-year survival for people in these age groups. DESIGN: We studied the 9-year (2002–11) mortality of adults aged ≥51 years with self-reported diabetes using the Health and Retirement Study Diabetes Mailout Survey (n=1,879). We dichotomized a composite measure of 5 self-reported diabetes care process measures defined as greater (3–5 processes) versus fewer (0–2 processes) care processes provided. SETTING: Health and Retirement Study (HRS). PARTICIPANTS: Respondents aged ≥51 years (n=1,879) with self-reported diabetes who completed both the Diabetes Mailout Survey and the core 2002 HRS survey. MEASUREMENTS: Cox Proportional Hazards model to test relationships between reported measures and mortality, controlling for socio-demographics, function, comorbidities, geriatric conditions, and insulin use. RESULTS: Baseline mean age was 68.8 (± 8.7) with 26.5% ≥75 years. Prevalence of each self-reported care process was 80.1%, 75.9%, 67.5%, 67.7%, and 48.2% for glycosylated hemoglobin testing, urine test, eye exam, aspirin counseling, and diabetes education, respectively. In 9 years, 32.1% respondents died. Greater care correlated with 24% less risk of dying (adjusted hazard ratio [aHR] = 0.76, 0.64–0.91). When respondents were age-stratified (≥ versus <75 years) improved survival was statistically significant only in the older age group. CONCLUSION: While we are unable to account for differences in adherence to care that may also affect survival, our study demonstrates that monitoring and counseling types of diabetes care processes are associated with long-term survival benefit even among older adults aged ≥75 with diabetes.